Set design in the Philippines does it help to determine the popularity of a television show? - De Leon, Ani Karina Sarabia; MAyo, Adelaida Villaraza (1995.)
Almost everyone watches television - the young, the old, intelligent or simple people alike. Why do we watch T.V.? There are a variety of reasons. Generally, people watch for entertainment. Some viewers watch to be updated on the latest news and information, some to see their favorite actors or programs, and there are still those who watch for lack of anything else to do. Whatever the reasons may be, no one can deny the realization that a lot of people are affected or influenced by what they see on T.V. Having established this fact, we now pose another question. What factors affect the popularity of a television program? We know that there are also a vast number of reasons for this. However, the condition in which this paper will focus on is Set Design in television and how it plays a part in the popularity of a program. It is assumed in the beginning of this paper that the majority of the television audience in the Philippine do not particularly watch the shows because they would do not particularly watch the shows because they would like to see the set design. I know this to be true because of experience, and it is unfortunate that it has to be so. Television is obviously a strong visual medium that major details such as set or production design should not be ignored. In a medium where almost everyone participates in, proper communication must be worked out from all angles possible, including this. I strongly believe that a good set design would not only help win the popularity of a television show, but in due time and with the proper educative and training goals towards the development of Philippine Set Design, it will improve the aesthetic and professional taste of the Philippine audience. We Filipinos are pround to boast of a unique cultural heritage, but it is discouraging to see what is happening to our movie and t.v. shows. To be objective enough, almost everything from the script, direction, down to the props are done in poor taste and with insufficient planning. Of course, there are some exceptions, and I commend these shows for giving that extra effort. Although I agree that to be able to influence the majority of the Philippine audience to watch T.V. because of the set design would be an astounding feat, it is not too much to hope that it may someday be. We are, after all, a very visually artistic people.
Thesis (BID)--University of the Philippines Diliman.
Keywords: Television -- Stage-setting and scenery -- Philippines